(untitled) (Sirte Journal of Medical Sciences, 2023)
Objective: The best way to treat (membranous forming) chronic subdural hematoma is unknown. Thus, the purpose of this study was to compare single burr-hole drainage with mini-craniotomy in the treatment of (membrane forming) chronic subdural hematoma, taking into account complication and recurrence rates. Method: (7) patients with (membrane forming) CSDH who underwent surgery between January 2018 and June 2022 had their clinical and radiologic records extracted. They account for 2,5% of all CSDH patients (18) treated during the same time period. The cases undergoing various types of surgery were compared in terms of clinical and radiological outcomes. Result: These (7) patients were divided into two groups: group A (4) patients underwent a single burr-hole trepanation, (3) patients underwent mini-craniotomy and (fenestration) membraneotomy, during all procedures, subdural drainage was placed and removed three days later. All patients recovered completely, with only one case in group A having a rest subdural collection and no complications in group B .Conclusion: When compared to burr-hole evacuation, the mini-craniotomy with (fenestration) membraneotomy technique may be superior for the treatment of (membranous forming) CSDH. More subdural space visibility is made possible by the mini-craniotomy, which also enables more aggressive fluid evacuation, better irrigation of the area, the safe fenestration of any membranes that are accessible. Despite the evident limitations of this study, an upcoming effort to evaluate this technique may be merited